Morphological assessment and characterization of uterine caruncles in Bengal goats - Hossain, Hafsa; Islam, Md. Rashedul; Maksuda Taslima; Mozahidul Islam Tuser; Nurjahan Akter Juli; Al Wasef; Mahfuzul Islam; Jahagir Alam (Universitas Airlangga, 2025)
This study aimed to evaluate and characterize the gross, histologic and ultrasonographic features of uterine caruncles in Bengal goats, an indigenous breed in Bangladesh. A total of 40 uteri were collected from sexually mature, pregnant and non-pregnant does obtained from local slaughter houses, preserved and processed in for gross morphological and histological characterization of uterine caruncles. Additionally, transabdominal ultrasonographic characterization of uterine caruncles were performed on randomly selected does at a commercial goat farm. Gross examination revealed multiple dome-shaped caruncles distributed along the endometrial surface, primarily arranged in four longitudinal rows. In both cyclic and non-cyclic goats, the average number of uterine caruncles was higher in the left uterine horn (55.85) compared to the right (54.42), with a consistent average of 4.30 rows observed in both horns. Histological examination of the caruncles revealed dense connective tissue, numerous blood vessels, and abundant uterine glands. The surface epithelium ranged from simple cuboidal to columnar. Morphometric analysis showed that the large caruncles were located in the mid-uterine horns. Transabdominal ultrasonography identified pregnancy in 7 of 20 does (35%) and visualized uterine cotyledons between days 32 and 40 of gestation. Measurement of cotyledons via ultrasound may serve as a reliable indicator of gestational age. These findings provide baseline data that may support reproductive research, enhance breeding management, and contribute to the assessment of reproductive performance and productivity of goats in Bangladesh.